Learning substrates in the primate prefrontal cortex and striatum: sustained activity related to successful actions - Histed, Mark H. (2009)
Learning from experience requires knowing whether a past action resulted in a desired outcome. The prefrontal cortex and basal ganglia are thought to play key roles in such learning of arbitrary stimulus-response associations. Previous studies have found neural activity in these areas, similar to dopaminergic neuron signals that transiently reflect whether a response is correct or incorrect. However, it is unclear how this transient activity, which fades in under a second, influences actions that occur much later. Here we report sustained outcome-related responses in single neurons of both areas, which last for several seconds until the next trial. Moreover, the outcome on a single trial influences the neural activity and behavior on the next trial: behavioral responses are more often correct and single neurons more accurately discriminate between the possible responses when the previous trial was correct. These long-lasting signals about trial outcome provide a way to link one action to the next, and may allow reward signals to be combined over time to implement successful learning.